2019
DOI: 10.1029/2019jb017871
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 Tenerife (Canary Islands) Long‐Period Seismic Swarm

Abstract: On 2 October 2016, a significant seismic swarm of long‐period events was recorded on Tenerife (Canary Islands, Spain). The swarm lasted more than 5 hr and consisted of at least 766 detected events. We found a positive correlation between the amplitude of each event and the preceding interevent time together with a stability of the spectral properties and waveform similarity during most of the swarm duration. Toward the end of the swarm, individual events merged into a continuous tremor. These observations can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…The seismological characteristics of the swarm indicated it was caused by a substantial injection of magmatic fluids into the hydrothermal system (D'Auria et al, 2019). Considering that during 2016 and 2017 no significant ground deformation was recorded on Tenerife, it is unlikely that the fluids originated from a shallow magmatic intrusion (D'Auria et al, 2019). Instead, D'Auria et al (2019) suggested the source was a small magma reservoir located beneath the seismic source, which released considerable amounts of magmatic fluid as a consequence of some instability or disturbance of the system.…”
Section: The 2016 Tenerife Long-period Seismic Swarmmentioning
confidence: 99%
See 4 more Smart Citations
“…The seismological characteristics of the swarm indicated it was caused by a substantial injection of magmatic fluids into the hydrothermal system (D'Auria et al, 2019). Considering that during 2016 and 2017 no significant ground deformation was recorded on Tenerife, it is unlikely that the fluids originated from a shallow magmatic intrusion (D'Auria et al, 2019). Instead, D'Auria et al (2019) suggested the source was a small magma reservoir located beneath the seismic source, which released considerable amounts of magmatic fluid as a consequence of some instability or disturbance of the system.…”
Section: The 2016 Tenerife Long-period Seismic Swarmmentioning
confidence: 99%
“…On October 2, 2016, a remarkable seismic swarm of long‐period events, starting at 13:16 UTC until 18:34 UTC of the same day (D'Auria et al., 2019) was recorded beneath Tenerife Island. This significant seismic event consisted of at least 766 discrete events; overlapping of events during the initial and final phases, formed a continuous volcanic tremor.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 3 more Smart Citations